Voltage-Dependent Dielectric Barrier Discharge Plasma Treatment of Oil-Palm EFB Combustion Exhaust: Coupled CO₂-CO Responses and Mechanistic Assessment of Oxygen-Forming Pathways - Rahmad Oktafiansyah; Gusti Atika Urfa; Andi Tessiwoja Tenri Ola; Suryajaya; Muhammad Fadhil Syahputra; Muhammad Aghil Surya Syahputra; Muhammad Afief Balya (Water, Air, & Soil Pollution, 2026)

Demineralization of marine biomass for catalytic upgrading of high-quality bio-oil production: A review - Pati Kemala; Lee Seng Hua; Rangabhashiyam Selvasembian; Ramesh Potnuri; Obie Farobie; Apip Amrullah; Harits Atika Ariyanta; Widya Fatriasari (Bioresource Technology Reports, 2026)

Modulation of functional properties, oxidative stability, and aroma evolution in cream-style salad dressing by Wolffia globosa powder incorporation - Sirima Sinthusamran; Chairat Techavuthiporn; Suriyan Supapvanich; Daimon Syukri; Yusti Atika; Panjit Pomasa (Food Chemistry, 2026)

Morphology and phylogeny reveal a New Species and Two New Combinations of Xerocomellus (Boletaceae) from Bajaur, Pakistan - Mohsin Ullah; Malka Saba; Syed Mohammad Tauseeq Ali Shah; Dege Zheng; Umer Rehman; Atika Noor; Muhammad Asif; Dong-Qin Dai; Ishtiaq Ahmad; Samantha C. Karunarathna (Current Microbiology, 2026)

Genomic Features of Stenotrophomonas rhizophila IS26 Suggest Potential for Aflatoxin B1 Reduction in Aspergillus flavus-Contaminated Maize - Guendouz Dif; Nadjette Djemouai; Hadj Ahmed Belaouni; Azzedine Abdi; Khadidja Ouled Hadj Youcef; Atika Meklat; Omrane Toumatia; Abdelghani Zitouni (Current Microbiology, 2026)

Deciphering the synergy of eudragit and polyethylene glycol supported cobalt oxide for catalytic, electrocatalytic and antibacterial activity: Computational insights - Atika; Muhammad Imran; Iram Shahzadi; Ali Haider; Sumaira Rasool; Anwar Ul-Hamid; Norah A. Albassami; Muhammad Ikram (Journal of Water Process Engineering, 2026)

Deep Learning Techniques for Precise Segmentation of Plant Species: Using Deeplabv3Plus-U-Net and UAV Imagery - Sara Badrouss; Mohamed Jibril Daiaeddine; El Mostafa Bachaoui; Mohamed Biniz; Hicham Mouncif; Atika Mouaddine; Abdessamad Hilali; Ilias Jennaoui; Abderrazak El Harti; Abdelali Boulli; Abderrahmene El Ghmari (Remote Sensing in Earth Systems Sciences, 2026)

New Host and Geographic Record of Lemuricola nycticebi in the Bengal Slow Loris - Joytu Kumar Mondal; Md. Rajiur Rahaman Rabbi; Mahir Anjum; M. Farhan Sadid Chowdhury; Ruhel Ahmed; Atiya Ibnat Lamia; Meherab Hossain; Atika Angum Miti; Chonchol Guala; Ibrahim Amin; Fahimuzzaman Nobel; Shahriar Caesar Rahman; et al. (Acta Parasitologica, 2026)

Biocontrol of Fusarium culmorum and enhanced wheat seedling growth by Streptomyces sp. D15 from Algerian steppe soil: performance and genome analysis - Omrane Toumatia; Guendouz Dif; Hadj Ahmed Belaouni; Sarah Mokhnache; Sid Ahmed Saadi; Yacine Goudjal; Atika Meklat; Noureddine Bouras; Abdelghani Zitouni (World Journal of Microbiology and Biotechnology, 2026)

Comprehensive phylogenomic analyses support the reclassification of several species belonging to the Deinococcus genus - Khaoula Bouznada; Rafika Saker; Hadj Ahmed Belaouni; Atika Meklat (Biologia, 2026)

Efficient cadmium sequestration from water using cotton husk biochar and copper oxide nanocomposite: adsorption performance, kinetics, and isotherm modeling - Atika Waqar; Muhammad Farhan; Faiza Sharif; Muhammad Imran; Ghulam Mustafa Shah (Environmental Geochemistry and Health, 2026)

Pension funds and sustainable investment: challenges and opportunities (Pension research Council Series), edited by P. Brett Hammond, Raimond Maurer, and Olivia S. Mitchell, new york: Oxford university Press, 2023, 418 pp., $90.00 (Hardcover), ISBN: 9780192889195 - Muhammad Noval; Atika Zahra Maulida; Faqih El Wafa (International Environmental Agreements: Politics, Law and Economics, 2026)

Upcycling eucalyptus kraft lignin into fluorescent graphene quantum dots for reproductive cell imaging in aquaculture biotechnology - Anna Octavera; Harits Atika Ariyanta; Khanesisya Luthfiyah Zahra; Diana Faoziah Hakim; Fajar Maulana; Novia Amalia Sholeha; Dian Hardiantho; Nurlatiha Khairun Nisa; Widya Fatriasari; Alimuddin (Bioresource Technology, 2026)

DNA barcoding and phylogenomics in mushrooms: current progress, challenges, and future prospects - Umer Rehman; Mehreen Sarfraz; Fouzia Bibi; Atika Noor; Mohsin Ullah; Entaj Tarafder; Zabta Khan Shinwari (Antonie van Leeuwenhoek, 2026)

Whole-genome sequencing of Nocardiopsis sp. B33, an alkali-halo-tolerant and moderately thermotolerant plant growth-promoting strain from Algerian Saharan soil: an in vitro and in silico study - Noureddine Bouras; Mónica Majo-Cuervo; Atika Meklat; Lorena Carro; Affaf Laassami; Esther Menéndez; Imen Nouioui (Biocatalysis and Agricultural Biotechnology, 2025)

Tissue Reconstruction and Drug Release System Utilizing Natural Polymer-Based Biomaterial Silk Fibroin: An Analysis Based on Traditional Chinese Medicine - Mahavir Chhajed; Atika Chhajed; Shrikant Joshi; Ishan Dubey; Ashish Pagariya; Deepak Joshi (Journal of Pharmaceutical Innovation, 2025)

A review of rice cultivation and cultivar development for high adaptability to global climate change - Nurul Jadid; Vira Octafiani; Triono Bagus Saputro; Kristanti Indah Purwani; Afifuddin Latif Adiredjo; Mochammad Roviq; Isnawati Isnawati; Fitriari Izzatunnisa Muhaimin; Siti Zubaidah; Yayuk Mulyati; Farapti Farapti; Atika Anif Prameswari; et al. (Journal of Crop Science and Biotechnology, 2025)

Analysis of Thermal and Hydrodynamic Behavior of Nanofluid Flow Through Porouse Cylindre in Stepped Channel with Elastic Upper Wall - Hanaa Derraz; Mohamed Bouzit; Atika Bencherif (Transport in Porous Media, 2025)

Genome‑Based Reclassification of Dactylosporangium matsuzakiense Shomura and Niida 1983 As A Later Heterotypic Synonym of Dactylosporangium vinaceum Shomura et al. 1983 and Proposal of Dactylosporangium vinaceum subsp. vinaceum subsp. nov. and Dactylosporangium vinaceum subsp. matsuzakiense subsp. nov - Rafik Ould taleb; Rafika Saker; Khaoula Bouznada; Hadj Ahmed Belaouni; Atika Meklat (Current Microbiology, 2025)

Whole-Genome-Based Reassessment of Saccharothrix Phylogeny, with the Proposal of Two New Subspecies: Saccharothrix longispora subsp. Longispora subsp. nov. and Saccharothrix longispora subsp. Yanglingensis subsp. nov., comb. nov - Guendouz Dif; Nadjette Djemouai; Noureddine Bouras; Atika Meklat; Abdelghani Zitouni (Current Microbiology, 2025)

Predicting and mapping soil saturated hydraulic conductivity in the Beni Moussa irrigated perimeter (Tadla Plain, Morocco) using Random Forest machine learning model - Atika Mouaddine; Ahmed Barakat; Soufiane Hajaj; Hassan Mosaid; Hicham Bouzekraoui; Zakaria Bni; Abdessamad Hilali (Modeling Earth Systems and Environment, 2025)

Phylogenomic analyses of the Listeriaceae family support species reclassification and proposal of a new family and new genera - Khaoula Bouznada; Hadj Ahmed Belaouni; Rafika Saker; Fawzia Chaabane Chaouch; Atika Meklat (Antonie van Leeuwenhoek, 2025)

Adaptive mechanisms of wheat cultivars to lead toxicity through enhanced oxidative defense, ionomic redistribution, and anatomical modifications - Muhammad Anas; Muhammad Saad Bashir; Khadija Saleem; Atika Noor; Umar Masood Quraishi (Journal of Plant Physiology, 2024)

Phenological pattern, breeding behaviour, and estimation of outcrossing rate in Grevillea robusta (Proteaceae) - Maneesh S. Bhandari; Aman Dabral; Anchal Bisht; Garima Mishra; Rajendra K. Meena; Rama Kant; Shailesh Pandey; Raman Nautiyal; Atika Chandra; Rajesh Tandon (The Nucleus, 2024)

Reproductive biology of Podostemum subulatum (Podostemaceae) reveals pre-anthesis cleistogamy - Priyanka Khanduri; Atika Chandra; Sudip Kumar Roy; Rajesh Tandon (Plant Systematics and Evolution, 2024)

Diversity and Bioactivity of Endophytic Actinobacteria Associated with the Roots of Artemisia herba-alba Asso from Algeria - Nadjette Djemouai; Atika Meklat; Khadidja Oulad Hadj Youcef; Asma Nacer; Sid Ahmed Saadi; Carol Verheecke-Vaessen (Current Microbiology, 2024)

I tap myself, and you tap me: bimanual predictive and reactive grip force control as a function of age - Sahian Numata; Atika Omerani; Catherine Mercier; Maxime T. Robert; Martin Simoneau (Experimental Brain Research, 2024)

Phylogenomic Analysis Supports the Reclassification of Caldicoprobacter faecalis (Winter et al. 1988) Bouanane-Darenfed et al. (2015) as a Later Heterotypic Synonym of Caldicoprobacter oshimai Yokoyama et al. (2010) - Khaoula Bouznada; Rafika Saker; Hadj Ahmed Belaouni; Atika Meklat (Current Microbiology, 2024)

Photocatalytic nanohybrid UV-light-driven PVDF/GO-NiFe@SiO2 membrane coupled with bentonite adsorption and ozonation process for a sustainable textile wastewater treatment - Tutuk Djoko Kusworo; Purwanto Purwanto; Bakti Jos; Budiyono Budiyono; Dewi Atika Puji Astuti; Achmad Maulana Arsyad Inamullah; Febio Dalanta (Process Safety and Environmental Protection, 2024)

Influence of Plant Growth Promoting Rhizobacteria (PGPR) on the Growth and Yield of Sunflower (Helianthus annus L.) Under Salt Stress - Shafi Ullah; Muhammad Ikram; Samina Sarfaraz; Ijaz ul Haq; Atika Khan; Zaryab Murad; Fazal Munsif (Journal of Crop Health, 2024)

Mycotoxin Accumulation in Dry Rot Potato Tubers from Algeria and Toxigenic Potential of Associated Isolates of Fusarium Genus - Sihem Hadjebar; Amine Yekkour; Nadjette Djemouai; Amina Matmoura; Maria Gutierrez-Pozo; Angel Medina; Atika Meklat; Carol Verheecke-Vaessen (Current Microbiology, 2024)

Advanced photocatalytic membrane GO-NiFe@SiO2/PVDF for efficient decontamination of synthetic dyes in batik wastewater with superior antifouling features - Tutuk Djoko Kusworo; Nita Aryanti; Achmad Maulana Arsyad Inamullah; Dewi Atika Puji Astuti; Dani Puji Utomo (Journal of Water Process Engineering, 2024)

Optimizing biological and physicochemical properties of acidic mine tailings through combined organo-mineral amendments and topsoil application - Atika Madline; Leila Benidire; Sofia I. A. Pereira; Hicham El khalil; Adam Michalski; Paula M. L. Castro; Przemysław Charzyński; Ali Boularbah (Journal of Soils and Sediments, 2024)

Dual Fluorimetric Sensor for Tandem Detection of Cadmium and Cysteine: An Approach for Designing a Molecular Keypad Lock System - Atika Farhi; Kaneez Fatima; Farha Firdaus (Journal of Fluorescence, 2024)

Development of genome-wide microsatellites from Primula denticulata and their utility in different species of the genus - Priyanka Yadav; Praveen Kumar Oraon; Dharmit Lepcha; Atika Chandra; Rajesh Tandon; Arun Chettri; Tanvir Ul Hassan Dar; Ratul Baishya; Mukund Dev Behera; Saroj K. Barik; Shailendra Goel (South African Journal of Botany, 2024)

Preparation of superhydrophobic biomedical pulp from rice straw coated with a stearic acid-cellulose composite - Irene Rizky Safina Daulay; Harits Atika Ariyanta; Azizatul Karimah; Fitria; Eko Budi Santoso; Antonius Herry Cahyana; Mohd Nadeem Shah Syed Bukhari; Mohammad Irfan Bakshi; Rudi Dungani; Tsabita Zahra Hanifa; Tati Karliati; Obie Farobie; et al. (Bioresource Technology Reports, 2024)

Nanotechnology-based theranostic and prophylactic approaches against SARS-CoV-2 - Atika Dhar; Sneh Lata Gupta; Pratima Saini; Kirti Sinha; Ankita Khandelwal; Rohit Tyagi; Alka Singh; Priyanka Sharma; Rishi Kumar Jaiswal (Immunologic Research, 2024)

Design of a simple bifunctional system as a self-assembled monolayer (SAM) for inverted tin-based perovskite solar cells - Atika Abid; Parameswaran Rajamanickam; Eric Wei-Guang Diau (Chemical Engineering Journal, 2023)

Actinobacteria: an underestimated source of potential microbial biocontrol agents against fusarium-related diseases in cultivated crops - Nadjette Djemouai; Atika Meklat; Amine Yekkour; Carol Verheecke-Vaessen (European Journal of Plant Pathology, 2023)

Genome-based reclassification of Kitasatospora niigatensis as a later heterotypic synonym of Kitasatospora cineracea Tajima et al. (2001) - Khaoula Bouznada; Hadj Ahmed Belaouni; Atika Meklat (Antonie van Leeuwenhoek, 2023)

Mechanochemical activation of palm kernel shell using the L9 Taguchi orthogonal array for carbon dioxide adsorption - Nor Adilla Rashidi; Yee Jack Lai; Mhd Syukri Atika Lakadir (Environmental Science and Pollution Research, 2023)

The Effect of Active Alkali and Sulfidity Loading on the Kraft Pulp Properties of Sweet Sorghum Bagasse - Azizatul Karimah; Nissa Nurfajrin Solihat; Novitri Hastuti; Maya Ismayati; Riksfardini Anissa Ermawar; Asma Sohail; Apri Heri Iswanto; Harits Atika Ariyanta; R. A. Ilyas; Rudi Dungani; Widya Fatriasari (Sugar Tech, 2023)

Centrifuge modeling on the effect of mechanical connection on the dynamic performance of narrow geosynthetic reinforced soil wall - Wen-Yi Hung; Ida Agustin Nomleni; Dicky Pratama Soegianto; Atika Praptawati (Geotextiles and Geomembranes, 2023)

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)

Recent Progress on the Development of lignin as future ingredient biobased cosmetics - Harits Atika Ariyanta; Eko Budi Santoso; Lisman Suryanegara; Enos Tangke Arung; Irawan Wijaya Kusuma; Mohamad Nurul Azman Mohammad Taib; M. Hazwan Hussin; Yeni Yanuar; Irmanida Batubara; Widya Fatriasari (Sustainable Chemistry and Pharmacy, 2023)

Focus group study on perceptions and information needs regarding vaccines targeting the older population: a cross-country comparison in four European countries - Manuela Dominique Wennekes; Renske Eilers; Antonella Caputo; Amandine Gagneux-Brunon; Riccardo Gavioli; Francesco Nicoli; Zoltán Vokó; Aura Timen; Amandine Gagneux-Brunon; Anna Czwarno; Antonella Caputo; Atika Abelin; et al. (GeroScience, 2023)
The increasing life expectancy leads to more older adults suffering from infectious diseases. Vaccines are available against diverse infections such as influenza, pneumococcal disease, herpes zoster and tetanus. However, vaccine acceptance is crucial for optimal preventive effect. The objective of the study is to perform a cross-country analysis of the perceptions and decision-making behaviour of older adults regarding vaccinations and their information needs. Focus groups with older adults were conducted in four countries: France, Hungary, Italy and the Netherlands. Data were analysed using thematic analysis. Demographic characteristics of participants were gathered with a questionnaire. Influenza and tetanus vaccines were commonly known, as was the disease influenza. On the contrary, the awareness of the vaccines against pneumococcal disease and herpes zoster were low. Participants also expressed a need for more information on vaccines, such as possible side effects, contra-indications and duration of protection, emphasizing that information is a condition for decision-making on vaccination. General practitioners were found to be the most important in information provision on vaccines. Perceptions on vaccines, such as effectiveness, side effects and safety, as well as perceptions on infectious diseases, such as severity, susceptibility and experiencing an infectious disease, played a role in the decision-making of older adults on vaccines. More awareness of the information needs among older adults with regard to vaccines should be raised among general practitioners and other healthcare providers. This requires appropriate knowledge about the vaccines among healthcare providers as well as communication skills to meet the information needs of older adults.

Nano packaging – Progress and future perspectives for food safety, and sustainability - Atika Ahmad; Ahsanulhaq Qurashi; David Sheehan (Food Packaging and Shelf Life, 2023)

Exploration of actinobacteria communities in seawater and sediments of mediterranean basin from Algerian coast displays hight diversity with new taxa and antibacterial potential - Amina Matmoura; Amine Yekkour; Mokhtaria Yasmina Boufadi; Noureddine Bouras; Abdelghani Zitouni; Salim Mokrane; Atika Meklat; Carol Verheecke-Vaessen (Biologia, 2023)

Isolation and characterization of five Purpureocillium strains from Algerian soils and assessment of their larvicidal activity against Culex pipiens (Diptera, Culicidae) - Rafik Ould Taleb; Fatma Sahir-halouane; Zoubir Harrat; Rafika Saker; Hadj Ahmed Belaouni; Amina Matmoura; Saïd Chaouki Boubidi; Noureddine Bouras; Atika Meklat; Carol Verheecke-vaessen (Biologia, 2022)

Assessment of producer’s perspective on the production of environmentally friendly fashion products: a case study in Indonesian natural dyes batik craftsmen - Adhi Kusumastuti; Atika; Taofan Ali Achmadi; Kongkiti Phusavat; Achmad Nizar Hidayanto (Environmental Science and Pollution Research, 2022)

Streptomyces species from the rhizosphere of the medicinal plant Artemisia herba-alba Asso: screening for biological activities - Nadjette Djemouai; Atika Meklat; Rabéa Gaceb-Terrak; Khadidja Oulad Hadj Youcef; Asma Nacer; Sid Ahmed Saadi; Somia Saad; Carol Verheecke-Vaessen; Noureddine Bouras (Biologia, 2022)

Genome-based reclassification of Actinopolyspora righensis Meklat et al. 2013 as a later heterotypic synonym of Actinopolyspora lacussalsi Guan et al. 2013 and description of Actinopolyspora lacussalsi subsp. lacussalsi subsp. nov. and Actinopolyspora lacussalsi subsp. righensis subsp. nov. - Rafika Saker; Noureddine Bouras; Atika Meklat; Michael D. Holtz; Hans-Peter Klenk; Imen Nouioui (Archives of Microbiology, 2022)

SOCS3 gene silencing does not occur through methylation and mutations in gastric cancer - Atika Al Saqri; Shika Hanif Malgundkar; Fatima Al Kindi; Ishita Gupta; Mansour Al Moundhri; Yahya Tamimi (Human Cell, 2022)

Prevalence and determinants of SARS-CoV-2 neutralizing antibodies in Lebanon - Omar Bahlawan; Rebecca Badra; Hanna Semaan; Nancy Fayad; Mina Nabil Kamel; Ahmed N. El Taweel; Mokhtar R. Gomaa; Abeer Sirawan; Atika Berry; Jacques Mokhbat; Jimi Goldstein; Jad Abdallah; et al. (Archives of Virology, 2022)

Chromatographic methods for the determination of a broad spectrum of UV filters in swimming pool water - Samia Mokh; Rania Nassar; Atika Berry; Mohammad El Khatib; Samah Doumiati; Mariam Taha; Raed Ezzeddine; Mohamad Al Iskandarani (Environmental Science and Pollution Research, 2022)

Protozoan Parasites and Leafy Greens in Marrakech: Study of Occurrence Using a Molecular Method - Salma Berrouch; Sandie Escotte-Binet; Atika Madline; Dominique Aubert; Eva Nast; Stéphanie La Carbona; Laila Hoummadi; Jamaleddine Hafid; Isabelle Villena (Acta Parasitologica, 2022)

Alleviation of salinity and metal stress using plant growth-promoting rhizobacteria isolated from semiarid Moroccan copper-mine soils - Atika Madline; Leila Benidire; Ali Boularbah (Environmental Science and Pollution Research, 2021)

The Association Between the Syrian Crisis and Cutaneous Leishmaniasis in Lebanon - Nazih A. Bizri; Walid Alam; Michel Khoury; Umayya Musharrafieh; Nada Ghosn; Atika Berri; Abdul Rahman Bizri (Acta Parasitologica, 2021)

Correction to: Molecular characterization of Trichoderma strains from West Sumatera, Indonesia and their benefcial efects on rice seedling growth - Azwir Anhar; Dwi Hilda Putri; Linda Advinda; Veby Atika; Syovia Amimi; Wahyu Aldo; Widya Ruchi (Journal of Crop Science and Biotechnology, 2021)

Molecular characterization of Trichoderma strains from West Sumatera, Indonesia and their beneficial effects on rice seedling growth - Azwir Anhar; Dwi Hilda Putri; Linda Advinda; Veby Atika; Syovia Amimi; Wahyu Aldo; Widya Ruchi (Journal of Crop Science and Biotechnology, 2021)

Indonesian Traditional Salted Fish: The Alteration Its Allergenicity during Processing - Nurheni Sri Palupi; Nindya Atika Indrastuti; Nur Wulandari (Journal of Aquatic Food Product Technology, 2021)

Regional modeling of soil sensitivity to water erosion in JIJEL region (Algeria) using MCA and GIS - Soumeya Atika Nehai; Mohamed Saïd Guettouche; Djouher Saadoud (Applied Geomatics, 2021)

Actinobacteria Associated with Vineyard Soils of Algeria: Classification, Antifungal Potential Against Grapevine Trunk Pathogens and Plant Growth-Promoting Features - Affaf Laassami; Amine Yekkour; Atika Meklat; Nadjette Djemouai; Abdelghani Zitouni; Salim Mokrane; Pascal Lecomte; Patrice Rey; Akila Berraf-Tebbal (Current Microbiology, 2020)

Soil loss estimation using the revised universal soil loss equation and a GIS-based model: a case study of Jijel Wilaya, Algeria - Soumeya Atika Nehaï; Mohamed Said Guettouche (Arabian Journal of Geosciences, 2020)

Composting of municipal solid waste by different methods improved the growth of vegetables and reduced the health risks of cadmium and lead - Ghulam Mustafa Shah; Nadia Tufail; Hafiz Faiq Bakhat; Iftikhar Ahmad; Muhammad Shahid; Hafiz Mohkum Hammad; Wajid Nasim; Atika Waqar; Muhammad Rizwan; Renjie Dong (Environmental Science and Pollution Research, 2019)

Identification of suitable internal control genes for transcriptional studies in Eleusine coracana under different abiotic stress conditions - Pradeep K. Jatav; Ankita Sharma; Dinesh K. Dahiya; Arif Khan; Atika Agarwal; S. L. Kothari; Sumita Kachhwaha (Physiology and Molecular Biology of Plants, 2018)

Governance challenges of cocoa partnership projects in Indonesia: seeking synergy in multi-stakeholder arrangements for sustainable agriculture - Atika Wijaya; Pieter Glasbergen; Pieter Leroy; Ari Darmastuti (Environment, Development and Sustainability, 2018)

Association of SNPs/haplotypes in promoter of TNF A and IL-10 gene together with life style factors in prostate cancer progression in Indian population - Kapil Bandil; Pallavi Singhal; Atika Dogra; Sudhir K. Rawal; D. C. Doval; Anil K. Varshney; Mausumi Bharadwaj (Inflammation Research, 2017)

Computational evaluation of 2-amino-5-sulphonamido-1,3,4-thiadiazoles as human carbonic anhydrase-IX inhibitors: an insight into the structural requirement for the anticancer activity against HEK 293 - Mahavir Chhajed; Anil K. Shrivastava; Atika Chhajed; Vijay Taile; Sumeet Prachand; Sanjay Jain (Medicinal Chemistry Research, 2017)

An angiotensin I-converting enzyme insertion/deletion polymorphism is associated with Pakistani asthmatic cases and controls - Nusrat Saba; Osman Yusuf; Sadia Rehman; Saeeda Munir; Sheeraz Ahmad; Atika Mansoor; Ghazala K Raja (Journal of Biosciences, 2016)

Thermoactinomyces khenchelensis sp. nov., a filamentous bacterium isolated from soil sediment of a terrestrial hot spring - Salim Mokrane; Noureddine Bouras; Atika Meklat; Abdelhadi Lahoum; Abdelghani Zitouni; Carol Verheecke; Florence Mathieu; Peter Schumann; Cathrin Spröer; Nasserdine Sabaou; Hans-Peter Klenk (Antonie van Leeuwenhoek, 2016)

Bounagaea algeriensis gen. nov., sp. nov., an extremely halophilic actinobacterium isolated from a Saharan soil of Algeria - Atika Meklat; Noureddine Bouras; Salim Mokrane; Abdelghani Zitouni; Peter Schumann; Cathrin Spröer; Hans-Peter Klenk; Nasserdine Sabaou (Antonie van Leeuwenhoek, 2015)

Deoxynivalenol-producing ability of Fusarium culmorum strains and their impact on infecting barley in Algeria - Amine Yekkour; Omrane Toumatia; Atika Meklat; Carol Verheecke; Nasserdine Sabaou; Abdelghani Zitouni; Florence Mathieu (World Journal of Microbiology and Biotechnology, 2015)

Actinopolyspora biskrensis sp. nov., a Novel Halophilic Actinomycete Isolated from Northern Sahara - Rafika Saker; Noureddine Bouras; Atika Meklat; Abdelghani Zitouni; Peter Schumann; Cathrin Spröer; Hans-Peter Klenk; Nasserdine Sabaou (Current Microbiology, 2015)

Nocardiopsis algeriensis sp. nov., an alkalitolerant actinomycete isolated from Saharan soil - Noureddine Bouras; Atika Meklat; Abdelghani Zitouni; Florence Mathieu; Peter Schumann; Cathrin Spröer; Nasserdine Sabaou; Hans-Peter Klenk (Antonie van Leeuwenhoek, 2015)

Tetralocular ovary and high silique width in yellow sarson lines of Brassica rapa (subspecies trilocularis) are due to a mutation in Bra034340 gene, a homologue of CLAVATA3 in Arabidopsis - Satish Kumar Yadava; Kumar Paritosh; Priya Panjabi-Massand; Vibha Gupta; Atika Chandra; Y. S. Sodhi; Akshay K. Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2014)

Streptomonospora algeriensis sp. nov., a halophilic actinomycete isolated from soil in Algeria - Atika Meklat; Noureddine Bouras; Amar Riba; Abdelghani Zitouni; Florence Mathieu; Manfred Rohde; Peter Schumann; Cathrin Spröer; Hans-Peter Klenk; Nasserdine Sabaou (Antonie van Leeuwenhoek, 2014)

Actinopolyspora righensis sp. nov., a novel halophilic actinomycete isolated from Saharan soil in Algeria - Atika Meklat; Noureddine Bouras; Abdelghani Zitouni; Florence Mathieu; Ahmed Lebrihi; Peter Schumann; Cathrin Spröer; Hans-Peter Klenk; Nasserdine Sabaou (Antonie van Leeuwenhoek, 2013)

Actinopolyspora saharensis sp. nov., a novel halophilic actinomycete isolated from a Saharan soil of Algeria - Atika Meklat; Noureddine Bouras; Abdelghani Zitouni; Florence Mathieu; Ahmed Lebrihi; Peter Schumann; Cathrin Spröer; Hans-Peter Klenk; Nasserdine Sabaou (Antonie van Leeuwenhoek, 2013)

Actinopolyspora algeriensis sp. nov., a novel halophilic actinomycete isolated from a Saharan soil - Atika Meklat; Noureddine Bouras; Abdelghani Zitouni; Florence Mathieu; Ahmed Lebrihi; Peter Schumann; Cathrin Spröer; Hans-Peter Klenk; Nasserdine Sabaou (Extremophiles, 2012)

Saccharothrix sp. PAL54, a new chloramphenicol-producing strain isolated from a Saharan soil - Adel Aouiche; Nasserdine Sabaou; Atika Meklat; Abdelghani Zitouni; Christian Bijani; Florence Mathieu; Ahmed Lebrihi (World Journal of Microbiology and Biotechnology, 2012)

Investigation of the Greek ancestry of populations from northern Pakistan - Atika Mansoor; Kehkashan Mazhar; Shagufta Khaliq; Abdul Hameed; Sadia Rehman; Saima Siddiqi; Myrto Papaioannou; L. L. Cavalli-Sforza; S. Qasim Mehdi; Qasim Ayub (Human Genetics, 2004)

Patterns of morphogenesis from cotyledon explants of pigeonpea - Atika Chandra; Vibha Gupta; Pradeep Burma; Deepak Pental (In Vitro Cellular & Developmental Biology - Plant, 2003)